PENGARUH PENGGUNAAN MEDIA INTERAKTIF, MEDIA GAMBAR, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA - Tandi, Martha; Rufi’i; Rachmadtullah, Reza (JS (JURNAL SEKOLAH), 2025)
Abstract: Abstract This study aims to analyze the effects of using interactive media and visual media as well as learning motivation on elementary students' mathematics learning outcomes. The research employed a quasi-experimental design with a 2 × 2 factorial arrangement. The population consisted of all fourth-grade students at SD Negeri Inpres Malompo, totaling 60 students, using cluster sampling techniques. The research instruments included a learning motivation questionnaire and a mathematics achievement test. Data analysis was conducted using two-way ANOVA after fulfilling normality and homogeneity assumptions. The results showed a significant difference in learning outcomes between students using interactive media and those using visual media, with interactive media demonstrating superior effectiveness. Furthermore, there was a significant difference in learning outcomes between students with high and low learning motivation. The analysis also revealed a significant interaction effect between the type of media and learning motivation, indicating that interactive media was most effective for students with high motivation. These findings highlight the importance of selecting appropriate instructional media and enhancing student motivation to improve mathematics learning outcomes. It is recommended that teachers optimally utilize interactive media and consider students' motivation to create more effective and engaging learning environments.  Keyword: interactive media, visual media, learning motivation, learning outcomes, mathematics.  Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan media interaktif dan media gambar serta motivasi belajar terhadap hasil belajar matematika siswa sekolah dasar. Desain penelitian yang digunakan adalah eksperimen semu dengan rancangan faktorial 2 × 2. Populasi penelitian adalah seluruh siswa kelas IV SD Negeri Inpres Malompo yang berjumlah 60 siswa, dengan teknik sampling cluster. Instrumen penelitian meliputi angket motivasi belajar dan tes prestasi belajar matematika. Analisis data dilakukan dengan ANOVA dua jalur setelah uji normalitas dan homogenitas terpenuhi. Hasil penelitian menunjukkan bahwa terdapat perbedaan signifikan hasil belajar antara siswa yang menggunakan media interaktif dan media gambar, di mana media interaktif memberikan hasil yang lebih baik. Selain itu, terdapat perbedaan signifikan hasil belajar antara siswa dengan motivasi tinggi dan motivasi rendah. Analisis juga menunjukkan adanya interaksi signifikan antara media pembelajaran dan motivasi belajar, yang mengindikasikan bahwa penggunaan media interaktif paling efektif pada siswa dengan motivasi tinggi. Temuan ini menegaskan pentingnya pemilihan media pembelajaran yang sesuai serta peningkatan motivasi siswa untuk meningkatkan hasil belajar matematika. Disarankan bagi guru untuk memanfaatkan media interaktif secara optimal dan memperhatikan aspek motivasi dalam pembelajaran. Kata Kunci: media interaktif, media gambar, motivasi belajar, hasil belajar, matematika